2022
DOI: 10.32479/ijeep.13211
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in Gasoline Price Transmission: How do Fuel Pricing Strategy and the Ethanol Addition Mandate Affect Consumers?

Abstract: This work aims at verifying the existence of asymmetries in gasoline price transmission between refining, distribution, and gas stations. The analysis covers two moments: before (2006-2016) and after (2016-2020) the new fuel pricing strategy adopted in the refining sector. Before 2016, gasoline prices in refineries were stable due to price intervention. After that, prices fluctuated in convergence with the international market. In this paper, we also consider ethanol prices. Due to an addition mandate, ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The results of this study indicated retail gasoline prices responded symmetrically to spot prices during and after the regulation. Raeder et al [12] evaluated a new fuel pricing strategy in the Brazilian fuel sector and found little changes with respect to pricing asymmetries before and after the new strategy. However, the welfare impact on consumers was more desirable after the changes.…”
Section: Literaturementioning
confidence: 99%
“…The results of this study indicated retail gasoline prices responded symmetrically to spot prices during and after the regulation. Raeder et al [12] evaluated a new fuel pricing strategy in the Brazilian fuel sector and found little changes with respect to pricing asymmetries before and after the new strategy. However, the welfare impact on consumers was more desirable after the changes.…”
Section: Literaturementioning
confidence: 99%